Pengaruh Kecukupan Modal, Efisiensi Operasional Dan Diversifikasi Pendapatan Terhadap Financial Sustainability - Viona Septiani; Etty Murwaningsari (JURNAL AKUNTANSI DAN AUDIT TRI BHAKTI, 2024)
Purpose – this study aims to gather empirical information on the factorsthat impact Financial Sustainability. The study emphasizes financialsustainability as the dependent variable, with capital adequacy ratio,operational efficiency, and revenue diversification as the independentvariables. This research focuses on analyzing conventional and shariageneral banking sub-sector companies that are publicly traded on theIndonesia Stock Exchange between 2020 and 2022.Design/methodology/approach – The sample method employs thepurposive sampling strategy. This study employs multiple regressionanalysis with the SPSS 22 application as a data analysis framework. Theresearch criteria covered a total of 40 commercial banks, comprising bothconventional and Islamic banks, based on the processed data. The researchdata is derived from secondary sources.Findings – Based on results of this study, it was found that the capitaladequacy and revenue diversification positively impact financialsustainability, however operational efficiency has a negative impact onfinancial sustainability.Research limitations/implications – For the conclusions that have beenput forward, researchers can provide some suggestions for improving thequality of further research. The suggestions proposed by the researcherinclude adding the number of other variables that are expected to affect thefinancial sustainability, then the company is advised to pay attention to thefactors that affect its financial sustainability.